Evaluation of Kinetics of Leaching of Lignins and Tannins in Batch Adsorption of Cr (VI) by Emblica officinalis Leaf Powder (EOLP) - Singh, Ram Pal; Zahra, Fatma (Journal of Membrane and Separation Technology, 2014)
The present paper is aimed to assess the contents of lignin and tannin leached in the batch adsorption test filtrate and to evaluate the kinetics of leaching of lignin and tannins. For the purpose, raw Emblica officinalis leaf powder (EOLP) has been used as adsorbent for removal of Cr (VI) from aqueous solution in batch mode of operation. Test results indicate that EOLP imparts lignin and tannin in batch test filtrate. Both lignin and tannin contents are related to pH, chemical oxygen demand (COD), initial Cr(VI) concentration (C0) residual Cr(VI) concentration in batch test filtrate (C),amount of adsorbent (Wad) and the time of contact (t). Dimensionless parameters are developed and the lignin and tannin contents are well correlated with dimensionless parameters. From the studies conducted on rate of leaching of both soluble lignin and tannins, the kinetics of leaching of soluble lignin and tannin follow a pseudo second order type rate kinetics. Linear regression models are developed based on pseudo second order kinetics for determination of lignin and tannin contents in batch test filtrate. However, these findings need further verification in future investigations.